The Impact of Social Media Marketing on Purchase Intention and the Mediating Role of Brand Awareness (Taman kopi Bali in Denpasar City Study) - Artha, Gde Egha Bramanta; Piartrini, Putu Saroyini (PT FORMOSA CENDEKIA GLOBAL, 2025)
The rise of coffee culture has transformed consumer behavior, shifting preferences from international chains to emerging local coffee brands such as Taman Kopi Bali. This study examines the the role that brand recognition plays as a mediator in the relationship between social media marketing and potential Taman Kopi customers' propensity to buy. A quantitative method was employed, involving 100 respondents from Dangin Puri Kelod Village in Denpasar City, selected through purposive sampling. Data were collected via offline questionnaires and analyzed using path analysis with SPSS 25.0. The data show the impact of social media marketing on purchase intention and brand identification is significant. Additionally, brand awareness influences purchase intent directly and acts as a partial mediator between buy intent and social media marketing. These findings suggest that increasing brand recognition through social media marketing might boost consumer purchase intentions. the value of digital interaction in increasing consumer interest and brand awareness.